The use of Callitriche cophocarpa Sendtn. for the reclamation of Cr-contaminated freshwater habitat: benefits and limitations - Augustynowicz, Joanna (Environ Sci Pollut Res Int, 2020)
This work is the first attempt to evaluate suitability of Callitriche cophocarpa Sendtn. (water-starwort) to remove Cr under real-world conditions. Our earlier laboratory-scale studies demonstrated outstanding hyperaccumulation properties of this aquatic higher plant (macrophyte) toward chromium in solution. We introduced C. cophocarpa plants into the watershed with sediments heavily polluted (on average 1400 mg/kg d.w. of Cr) by a tannery. The plants grew vigorously and exhibited no physiological or anatomical disorders. Based on chemical fractionations of bottom sediments, we found low Cr bioavailability. The element was strongly associated with the sediments and could be classified into the following fractions (%): oxidizable III (68.2) > residual IV (28.8) > reducible II (1.6) > exchangeable I (1.4). Despite this, Cr content in plant organs at the contaminated sites was 33 up to 83 times greater than in the control leaf/stem and roots, respectively. Altering redox potential during, i.e., sediment deposition on land may change chemical forms of bound metals in a solid phase, and thus further increase Cr phytoextraction by plants. With this in mind, we concluded that the species, being an outstanding Cr accumulator under laboratory conditions, can be useful in the reclamation of Cr-polluted sediments under controlled, oxidizing conditions.